Team performance in space crews: Houston, we have a teamwork problem. (August 2019) - Larson, Lindsay; Wojcik, Harrison; Gokhman, Ilya; DeChurch, Leslie; Bell, Suzanne; Contractor, Noshir
Abstract: Space crews venturing beyond low Earth orbit will experience unprecedented levels of autonomy and unpredictable challenges. Mission success will require effective teamwork. How do teamwork capabilities change over time in isolation and confinement? To explore this question, 4, 4-member crews who participated in the 30-day campaign of the National Aeronautics and Space Agency (NASA)'s Human Exploration Research Analog (HERA) were observed. Crews endured isolation, confinement, and communication delays. Teamwork capabilities were observed along four critical dimensions: generate (creativity tasks), choose (intellective tasks), negotiate (cognitive conflict tasks), and execute (psychomotor tasks). A battery of team task was administered requiring the crew to generate, to choose, and to negotiate. Execute performance was assessed using NASA's multi-mission space exploration vehicle (MMSEV) task. Team task batteries were performed on Mission Days 11, 16, and 30. Execute performance was assessed on 18 of 30 days. Findings show behavioral team performance (cognitive conflict and psychomotor tasks) increases over time, whereas conceptual team performance (creativity and intellective tasks) declines. Implications of these results were considered for future research and the design of countermeasures that support crew functioning. Highlights: Space crew performance is multi-dimensional. Crew performance changes over time in extended isolation and confinement. Analog crews improve on psychomotor task performance over time. Analog crews decline on creativity tasks and intellective tasks over time. Behavioral and conceptual performance are affected differently by isolation.